2022
DOI: 10.1155/2022/1365526
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Jatropha variegata Fruits as a Natural Contraceptive: Antifertility Activity and Phytochemical Analysis

Abstract: Background. Jatropha variegata (family, Euphorbiaceae) is native to Yemen, where it is commonly known as the Ebki shrub. The fruits of the plant are traditionally ingested by local women as a natural method of contraception. This study was undertaken to investigate the phytochemical content of the methanol extract of J. variegata fruits and to evaluate its antifertility potential. Methods. Isolation of the chemical constituents was performed by chromatographic techniques, and the chemical structures of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, in a methanolic extract obtained by ultrasound from J. curcas seeds, Thi et al [ 25 ] identified fatty acids. Alhaj et al [ 27 ] identified fatty esters and fatty acids (palmitic acid) with anti-infertility activity in a methanolic extract from the fruit of J. variegate , which correspond to the chemical groups and bioactive compounds found in the methanolic extract of J. cordata bark.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in a methanolic extract obtained by ultrasound from J. curcas seeds, Thi et al [ 25 ] identified fatty acids. Alhaj et al [ 27 ] identified fatty esters and fatty acids (palmitic acid) with anti-infertility activity in a methanolic extract from the fruit of J. variegate , which correspond to the chemical groups and bioactive compounds found in the methanolic extract of J. cordata bark.…”
Section: Resultsmentioning
confidence: 99%
“…2022), and J. variegata Vahl (Alhaj et al . 2022). Alkaloids, coumarins, flavonoids, lignins, phenols, saponins, steroids, tannins, and terpenoids were also found in extracts of J. gossypiifolia L. (Félix‐Silva et al .…”
Section: Discussionmentioning
confidence: 99%
“…Its fruit methanol extracts exhibit estrogenic activity and successfully prevent embryo implantation. [36] Plants such as Mondia whitei, Acalypha villicaulis, Combretum illairii, Erythrina abyssinica, Pappea capensis, Rhus vulgaris, and Warburgia ugandensis are the most commonly used, while the most commonly used organs for making decoctions (69%), are roots (44.9%), leaves (21.8%), stem and root barks (16.7%) of shrubs (35%), trees (31%), herbs (26%), and climbers (8%). Among the plants that help raise testosterone levels and produce pro-sexual stimulatory effects in male rats are Citropsis articulata, Cola acuminata, Ekebergia capensis, Plumbago zeylanica, Tarenna graveolens, Urtica massaica, and Zingiber officinale [Table 2].…”
Section: Anti-ovulation Activitymentioning
confidence: 99%